2006
DOI: 10.1002/ca.20285
|View full text |Cite
|
Sign up to set email alerts
|

A case of an accessory brachialis muscle

Abstract: Functionally, the brachialis muscle serves a critical role as the primary flexor of the arm at the elbow. However, few reports exist in the literature, which describe variations of this muscle. We present a case of an accessory brachialis muscle (AcBr), found during routine dissection at Harvard Medical School during 2003. The AcBr originated medially from the mid-shaft of the humerus and the medial intermuscular septum. During its course medially, toward the elbow, the AcBr crossed both the brachial artery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 3 publications
1
17
0
1
Order By: Relevance
“…Our findings were very much similar to that of Loukas et al, 4 who observed a case of an accessory brachialis muscle that originated from the medial side of the mid shaft of the humerus along with the medial intermuscular septum. It crossed both the brachial artery and the median nerve during its course.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were very much similar to that of Loukas et al, 4 who observed a case of an accessory brachialis muscle that originated from the medial side of the mid shaft of the humerus along with the medial intermuscular septum. It crossed both the brachial artery and the median nerve during its course.…”
Section: Discussionsupporting
confidence: 92%
“…(8,10) Loukas et al reported a case of bilateral accessory digastric muscles, which originated from the digastric fossa of their respective sidesthe left one was inserted into the midline raphe of the mylohyoid muscle, while the right one immediately bifurcated into two heads. (3) The lateral head rejoined the main belly of the digastric muscle, while the medial head inserted into the midline raphe of the mylohyoid muscle. (3) In the present study, however, the accessory muscle was bilaterally symmetrical.…”
Section: Discussionmentioning
confidence: 99%
“…(3) The lateral head rejoined the main belly of the digastric muscle, while the medial head inserted into the midline raphe of the mylohyoid muscle. (3) In the present study, however, the accessory muscle was bilaterally symmetrical.…”
Section: Discussionmentioning
confidence: 99%
“…George & Nayak (2008), found a case of an acBr that merged with the superficial flexors of the forearm and partly inserted to the olecranon process. Loukas M et al (2006), published a case of an acBr that took origin from mid shaft of humerus and the medial intermuscular septum.…”
Section: Discussionmentioning
confidence: 99%